Analisis Penerapan Anggaran Fleksibel sebagai Alat Perencanaan dan Pengendalian Biaya: Studi Literatur - Nadia Saragih; Meilany Putri Effendi; Herikson Muksa Putra Sitanggang (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2026)
This study examined the application of flexible budgeting as a strategic tool for cost planning and control within organizational management. The primary problem addressed was the inherent limitation of static budgets in accommodating fluctuations in activity levels, which often led to inaccurate financial evaluations and inefficient resource allocation. A literature review approach was employed to synthesize various theoretical frameworks and empirical findings regarding the implementation of dynamic budgetary systems. The analysis focused on how flexible budgets adjusted planned costs based on actual volume changes, thereby providing a more realistic benchmark for performance measurement. The findings indicated that flexible budgeting significantly enhanced the accuracy of variance analysis by distinguishing between controllable and uncontrollable cost deviations. Furthermore, the results demonstrated that this approach facilitated better decision-making processes and improved operational efficiency by providing management with adaptable financial guidance. In conclusion, the integration of flexible budgets was found to be an effective mechanism for maintaining financial discipline and achieving organizational objectives in volatile economic environments.